STRUCTURAL AND FUNCTIONAL FEATURES OF THE LEFT VENTRICLE IN PATIENTS WITH HEART FAILUREIN ISCHEMIC HEART DISEASE AND THYROTOXICOSIS - Khusainova Munira Alisherovna; Ibodulloyeva Marjona Habibulloyevna; Rabbimova Fariza Voxidovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT Goal. To determine the structural and functional features of the left ventricle in patients with chronic heart failure with coronary heart disease and thyrotoxicosis. Materials and methods. 85 patients aged 58.3±5.6 years were divided into 3 groups: the main group consisted of 25 patients with coronary heart disease (CHD), chronic heart failure (CHF) of functional classes II−III (FC) and thyrotoxicosis, the average age was 59.23±3.81; the 1st comparison group consisted of 30 patients with CHD, HSN FC II-III, without thyroid pathology, average age – 57.6±2.73; comparison group 2 – 30 patients with thyrotoxicosis without concomitant cardiovascular diseases (CVD), average age – 45.4±3.51. The structure and function of the thyroid gland were studied in all patients, and an echocardiographic (EchoCG) study was performed to assess the structural and functional parameters of the left ventricle (LV). Results. Pathological LV remodeling in patients of the main group is represented by two types: concentric LV hypertrophy (LVH) and eccentric LV hypertrophy (LVH), and LVH was more common than in patients without thyroid pathology with CHF on the background of coronary heart disease (84.0%, p=0.01). The contractility of the LV myocardium in patients of both groups with CHF was reduced, the values of the ejection fraction corresponded to the intermediate type of HF, there was no significant difference between the indicators (p=0.1). In the main The group of patients showed a significantly more pronounced decrease in the ratio of the blood flow rate of early LV diastolic filling and the maximum rate of atrial systole (E/A) – 0.63 and an increase in isovolumetric relaxation time (IVRT) – 84.69 ms compared with the indicators of patients with ischemic heart failure without thyroid pathology (p=0.021; p=0.034). Conclusion. For patients with CHF on the background of coronary heart disease and thyrotoxicosis, the predominance of remodeling is characteristic LV by type of LVL (84.0% of cases), moderate decrease in LV contractility and more pronounced diastolic dysfunction, which determines the structural and functional features of LV in patients with CHF in the presence of this comorbidity.